Convergent Acquired Strabismus Fixus in High Myopia Patient- an Overview (Journal of National Institute of Ophthalmology, 2026)
Purpose: To identify and report such rare entity and keep special concern to manage such case. Method: It is a prospective study. We hereby reviewed six cases of this rare entity selected from pediatric outpatient department of Ispahani Islamia Eye Institute & hospital since January ’2019- December’2019. Selected patients underwent detailed history taking, cyclo refraction, slit lamp examination, orthoptic evaluation, fundoscopy and nystagmus evaluation. Result: Average age of presentation was 8+/-2 years. Aided visual acuity of two patients was (3/60-6/60), three (6/60-6/24), one (6/24-6/12). Four patients had positive family history of high myopia. On slit lamp examination revealed deep anterior chamber. One case showed normal fundus where remaining fives had characteristic myopic fundus. Four were associated with jerky nystagmus. Three of them had right beating and one left beating nystagmus. Head tilt was present in one patient. Ocular motility was free for two cases whereas restricted in variable degree in four cases may be due to herniation of progressive enlarging myopic globe supero temporally and retro equatorially through muscle cone. Conclusion: Understanding the different spectrum of presentation of high myopic patient facilitates early diagnosis, rehabilitation and management of such patient.J.Natl.Inst.Ophthalmol.2024;7(2): 71-75